A facile and industrially feasible one-pot approach to prepare graphene-decorated PVC particles and their application in multifunctional PVC/graphene composites with segregated structure. (15th March 2020) - Wang, Libing; Wei, Xinyi; Wang, Gang; Zhao, Shuai; Cui, Jian; Gao, Ailin; Zhang, Guangfa; Yan, Yehai
Abstract: Direct hot compression of fillers-decorated polymer particles is the simplest and most developed method for the construction of segregated composites. Herein, graphene was uniformly and firmly decorated onto the surface of polyvinyl chloride (PVC) particles synthesized by suspension polymerization via vitamin C (Vc) reduction of graphene oxides (GO). Since the risky and complex change of the synthesis process of PVC is avoided, a facile and industrially feasible one-pot approach to prepare reduced GO (RGO) decorated PVC (RGO@PVC) is established. And then, the segregated PVC/graphene nanocomposites (s-PVCG) were prepared by direct hot compression of RGO@PVC. In comparison with the neat PVC and the random PVCG (r-PVCG), s-PVCG show remarkably improvement in electrical conductivity (σ), thermal conductivity (λ), thermal stability and flame retardation. The percolation threshold of σ (ϕc ) for s-PVCG is as low as 0.012 vol%, and the ultimate σ (σmax ) of s-PVCG attains 10 −2 S cm −1 after 2.0 wt% RGO loading. At 4.1 wt% RGO loading, λ, the temperature of maximum weight loss (Tmax ) and limited oxygen index (LOI) of s-PVCG are improved by 75%, 21 °C and 4 relative to the neat PVC, respectively.